Assessing the Effectiveness of Technology in Destination Marketing during the COVID-19 Pandemic - Chuchu, Tinashe (E-Journal of Tourism; Volume 8 Number 2 (September 2021)DO - 10.24922/eot.v8i2.74597, 2021)
Technology has played an important role in tourism and the COVID-19 pandemic expanded this role as well as its importance. This research therefore explores the impact that technology made in destination marketing during the time of the pandemic. This research explores the pandemic’s first year of widespread global coverage both in the media and in academic literature. An extensive review of technology use in destination marketing and COVID-19’s impact on destination marketing is conducted. The present research is mainly concerned with the first year of the pandemic but is not limited to that period since the adoption of technology in tourism existed before the pandemic but increased due to the pandemic. This research made every attempt to investigate this phenomenon. Based on findings of the research, future research direction is proposed.